Study on the Application of the Concrete Model in PLAXIS to Bangkok Clay Improved with Portland Cement - Soe Thinzar Than; Anantanasakul, Pongpipat (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Ground improvement by admixing the natural soil with Portland cement is one of the effective soil treatment techniques to improve the engineering properties of soft Bangkok clay. The objective of this study is to investigate the application of the Concrete Model in PLAXIS for cement-treated Bangkok clay. The Concrete Model is a constitutive model which has the features to simulate the non-linear behavior of cementitious materials both in the hardening and softening regimes. This study presents the formulation and calibration of the Concrete Model, particularly for cement-treated cohesive soils. The time- independent strength and stiffness parameters for the Concrete Model are calibrated from the laboratory unconfined compression tests and undrained triaxial compression tests of cement-treated Bangkok clay. The relationships between the undrained stiffness and shear strength parameters and cement content and water-cement ratio are discussed. The applicability of the Concrete Model for cement treated Bangkok clay is assessed. The SoilTest feature in PLAXIS finite element software is employed to calibrate the relevant model parameters. Parameter values for the Concrete Model and laboratory experiments that result in accurate simulation of the behavior of cement-treated Bangkok clay are provided and discussed.